PENGARUH REWARD DAN LOYALITAS KARYAWAN TERHADAP MOTIVASI KERJA KARYAWAN PT. TUAHTA MAJU ERSADA - Jesica Halim; Syawaluddin Syawaluddin; Aidil Putra (STIE-PMCI, 2020)
Abstract. PT. Tuahta Maju Ersada is a company engaged in the field of mini PKS (Palm Oil Mill), which has been established since 2008. A good and high reward will motivate employees and low employee loyalty greatly affects employee motivation. The purpose of this study was to determine the effect of employee reward and loyalty on the work motivation of PT. Tuahta Advanced Ersada.The research method used is a quantitative analysis method. The data used are primary and secondary data. The study population was 50 people using saturated sampling techniques where all members of the population were sampled. Variables are measured with a Likert scale. The data analysis technique used is multiple linear regression.Based on simultaneous analysis of employee rewards and loyalty affect the work motivation of employees of PT. Tuahta Advanced Ersada. Partially, there is the effect of reward variables on employee work motivation and there is an influence of employee loyalty on the work motivation of employees of PT. Tuahta Advanced Ersada.Keywords: Employee Reward, Employee Loyalty, Employee Work Motivation.